That's going to depend on the values of 'm' and 'p'. As soon as either
of them changes, the value of (5m + 3p) instantly changes.
5m-5n+5m+5n When simplified: 10m
3p+7 = 16+2p 3p-2p = 16-7 p = 9
8 + 5p + 7q + 9 + 3p Reordering: 8 + 9 + 5p + 3p + 7q Combine like terms: 17 + 8p + 7q
-5 + 3p - p = -5 + 2p
3p + 6p = (3 + 6)p = 9p
5m-5n+5m+5n When simplified: 10m
3p
3p
-7m - 3m + 5m = -5m
3p+52
3p+7 = 16+2p 3p-2p = 16-7 p = 9
3p+5+p = -23 3p+p = -23-5 4p = -28 p = -7
8 + 5p + 7q + 9 + 3p Reordering: 8 + 9 + 5p + 3p + 7q Combine like terms: 17 + 8p + 7q
5m - 6 + m + 10 = 6m + 4
5m-3x+3m+2x 2m-x
-5 + 3p - p = -5 + 2p
Add them together: 02p+3p = 5p